PENGGUNAAN SISTEM INFORMASI GEOGRAFIS DAN CITRA IKONOS UNTUK KAJIAN PEMODELAN LOKASI ALTERNATIF KOLAM PEMBUANGAN LUMPUR LAPINDO DI SIDOARJO JAWA TIMUR - Firman Farid Muhsoni; H Hartono; S Sigit (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2010)
Geographic Infiormation System modeling can be used to predict inundated area expansion that caused by mud flow. The alternative location of Lapindo mud flow can be identified from inundated area prediction. The aims of this research are 1) to appraise the accuracy of elevation data interpolation methods and IKONOS imagery accuracy in determinant variable retrieval, 2) to determine the alternative pond of Lapindo mud flow, 3) to evaluate volume capacity and to analyze the construction cost.The method of this research consist of determinant variable retrieval, these are: inundated zone, land use, public facilities and impacted area. Inundated zone map was retrieved from DEM interpolation result, the watershed modeling was done to get flow accumulation, flow direction and watershed, in order to get inundated zone. Land use map and public facilities were obtained from IKONOS imagery visual interpretation. Impacted area was determined according to President Regulation No. 14, 2007. Scoring, weighting and overlay of these four maps have been made to get mud flow alternative location. Weighting factors have been retrieved according to questioner result.The result of this research has shown that Kriging interpolation method was the best method for elevation data interpolation (RMSE = 1.3565). Land use interpretation accuracy achieves 93.5%. Public facilities interpretation accuracy achieves 100%. Nine candidates of mud exile alternative pond have been got as a research result. Alternative pond No.1 is the best pond, with 4.027 Ha area. Volume pond capacity achieves to 564.599.751 m3, with 3.704 days or 10 years endurance. Total co[1]st of pond construction achieves Rp. 7.276.313.970.000. Keywords: site selection, watershed, mud, Lapindo.